Buyer market power, transport mode, and exchange rate shocks - Davide Del Prete; Aminur Rahman; Edoardo Tolva (Asian Development Bank (ADB), 2025)
This paper studies how international buyers' market power and transport mode shape the pass-through of exchange rate shocks to export prices. Using transaction level customs data from the Bangladeshi garment sector, we first document substantial buyer market power and the concentration of export activity in key trade hubs that shape transport decisions. We then show that large buyers leverage both their market power and their reliance on air freight to mitigate the impact of exchange rate fluctuations. Taken together, our findings highlight how buyer characteristics shape exporters' adjustment to external shocks, with broader implications for regional economic resilience.
Keywords: D22; D43; E31; F10; L14; L22; 330; Bangladesh; exchange rate; global value chain; market power; transport mode